Tipidum Unit Strategy in Enforcing Online Fraud Criminal Laws in Sidoarjo Polresta - Pramono, arief satrio (Advances in Police Science Research Journal, 2024)
The criminal act of online fraud is the most serious and public problem that frequently occurs in the Indonesian region, especially in the Sidoarjo Police Department area. Preliminary data obtained from the Sidoarjo Police Criminal Investigation Unit shows that in the period 2020 to 2023 there was a significant increase in online fraud cases handled by the Sidoarjo Police Criminal Investigation Unit. This research was conducted with the aim of describing the law enforcement of online fraud crimes, finding factors that influence the law enforcement of online fraud crimes, and determining the Ipidum unit’s strategy in enforcing the law on online fraud crimes at the ISidoarjo police station. This research uses a review of research literature and conceptual literature. The method used is field research with a qualitative approach through interviews, observation and document review. The research results show that dealing with criminal acts of online fraud includes receiving reports from the public, carrying out investigations, carrying out investigations and submitting case files and suspects to the Prosecutor’s Office. There are internal and external factors that influence the law enforcement of criminal acts of online fraud and the efforts made by the Sidoarjo Police to deal with these criminal acts are by conducting outreach to the community, conducting inquiries and investigations and optimizing cooperation with related agencies.